Analyse des associations végétales de la plaine salée du Bas-Cheliff, Algerie - Adda, Ababou; Mohammed, Chouieb; Mohamed, Khader; Khalladi, Mederbal; Zineddine, Bentayeb; Djamel, Saidi (Acta Biológica Paranaense, 2009)
Analyse des associations végétales de la plaine salée du Bas-Cheliff, Algerie